Efecto de tres niveles de fertilización química en el comportamiento y rendimiento de dos variedades de haba (vicia faba l.) en la zona de la Libertad, Provincia del Carchi - Erazo Recalde, Luis Álvaro (2011)
The titled investigation "effect of three levels of chemical fertilization in the behavior and yield of two bean varieties (Vicia faba l.), it was developed in the area of the freedom, county of the Carchi", in San Francisco's sector, located in the canton Mirror, county of the Carchi, to an altitude of 3000 m.s.n.m, with an annual half temperature of 12 ºC, relative humidity of 80%, and an annual half precipitation of 1200 mm, the investigation was carried out during the months of May to November of the 2010, with the objective of determining the effect of the application of chemical fertilizers in the agronomic behavior of the bean cultivation in the Canton Mirror, County of the Carchi. The factors in study were the fertilizer doses N 21 P 100 K 25 S 25, N 17 P 80 K 20 S 20 and N 13 P 60 K 15 S 15 more an absolute witness applied to the two varieties (Chaucha and Guaba), giving a total of eight treatments